Implementasi Kebijakan Pengelolaan Sampah Perkotaan di Kota Manado - Jericho Danga Pombengi; Joyce Jacinta Rares; Stevania Sajow; Fibrianti Kaparang; Suci A Tamrin; Yulinda Tinungki (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This research seeks to assess how urban waste management regulations are being executed in Manado City. Due to the swift rise in population, urban development, and growing economic activities, waste management has emerged as a critical concern in city governance, leading to increased waste production. A descriptive qualitative methodology is utilized in this study, drawing on secondary data sourced from government publications, statistical data, policy papers, and pertinent academic research. The evaluation uses George C. Edward III’s framework for policy implementation, emphasizing aspects such as communication, available resources, readiness, and organizational setup. Results show that the execution of waste management strategies in Manado City has not yet reached optimal levels. The city produces roughly 300 to 330 tons of waste daily, which puts considerable strain on the waste management system, particularly affecting the Sumompo landfill. Several key challenges have been noted, including insufficient infrastructure, a lack of skilled human resources, poor coordination among agencies, minimal community involvement, and low application of waste processing technologies. Additionally, this study highlights that issues related to waste management extend beyond technical challenges, also encompassing institutional capabilities and community attitudes. Consequently, enhancing communication efforts, improving resource oversight, bolstering inter-agency collaboration, increasing public involvement, and advocating for sustainable waste management approaches are vital for boosting the effectiveness of urban waste management strategies in Manado City.